Acupuncture for Post-stroke Shoulder-Hand Syndrome: A Systematic Review and Meta-Analysis - Liu, Shaonan; Zhang, Claire Shuiqing; Cai, Yiyi; Guo, Xinfeng; Zhang, Anthony Lin; Xue, Charlie Changli; Lu, Chuanjian (Frontiers in Neurology, 2019)
Background: Shoulder-hand syndrome (SHS) is prevalent in hemiplegic patients after stroke. Potential benefits of acupuncture were shown in recent clinical trials. This systematic review aimed to comprehensively evaluate the safety and efficacy of acupuncture for SHS in stroke patients. Methods: Five English databases (PubMed, Embase, CINAHL, CENTRAL and AMED) and four Chinese databases (CBM, CNKI, CQVIP and Wanfang) were searched from their inceptions to January 2019. Randomized, controlled trials that evaluated the add-on effects of acupuncture to rehabilitation for post-stroke SHS were identified. Results: Thirty-eight studies involving 3,184 participants fulfilled the eligible criteria and were included in the review. The overall meta-analysis showed that acupuncture combined with rehabilitation significantly improved motor function (upper-limb Fugl-Meyer Assessment (FMA): 34 studies, mean difference (MD) 8.01, 95% confidence interval (CI) [6.69,9.33]), and reduced pain (visual analogue scale (VAS): 25 studies, MD –1.59, 95%CI [–1.86,–1.32]). It also improved activities of daily living (ADL) when compared with rehabilitation alone (ADL: 11 studies, MD 9.99, 95%CI [5.91,14.06]). However, the certainty of evidence of all these outcomes was assessed as ‘low’. Subgroup analyses of acupuncture stimulation types and treatment duration all showed significant add-on effects comparing with rehabilitation alone. The safety of acupuncture was unclear because there is a lack of detailed reporting of adverse events in most of the included studies. Conclusions: Acupuncture therapy seems effective for motor function, pain relief and activities of daily living in stroke patients with mild SHS, when it is used in combination with rehabilitation. The low certainty of evidence downgrades our confidence in making recommendations to clinical practice.